New insights into population structure of the European golden eagle (Aquila chrysaetos) revealed by microsatellite analysis. (29th September 2019) - Nebel, Carina; Gamauf, Anita; Haring, Elisabeth; Segelbacher, Gernot; Väli, Ülo; Villers, Alexandre; Zachos, Frank E
Abstract: Connectivity between golden eagle ( Aquila chrysaetos ) populations is poorly understood. Field studies exploring natal dispersal suggest that this raptor is a philopatric species, but with the ability to roam far. However, little is known about the population structure of the species in Europe. Our study is based on 14 microsatellite loci and is complemented by new and previously published mitochondrial control region DNA data. The present dataset includes 121 eagles from Scotland, Norway, Finland, Estonia, the Mediterranean and Alpine regions. Our sampling focused on the Alpine and Mediterranean populations because both mitochondrial DNA (mtDNA) lineages found in golden eagles, the Holarctic and the Mediterranean, are known to co-occur there. Cluster analyses of nuclear DNA support a shallow split into northern and southern populations in Europe, similar to the distribution of the two mtDNA lineages, with the Holarctic lineage occurring in the north and the Mediterranean lineage predominating in the south. Additionally, Scotland shows significant differentiation and low relative migration levels that indicate isolation from the mainland populations. Alpine and Mediterranean golden eagles do not show nuclear structure corresponding to divergent mtDNA lineages. This indicates that the presence of northern Holarctic mitochondrial haplotypes in the Alps and the Mediterranean is attributable to past admixture rather than recent long-distance dispersal.